PENERAPAN PENGHITUNGAN, PENYETORAN, DAN PELAPORAN PPH PASAL 21 TAHUNAN, TERHADAP KEWAJIBAN PAJAK ORANG PRIBADI - Amar, Siti Salama (Fakultas Ekonomi, Program Studi Akuntansi, 2018)
Income tax is one of the taxes collected by Kantor Pelayanan Pajak Pratama Pamekasan, te better the level of colculation, payment, deduction and tax reporting carried out by individual taxpayers, the better the participation of the community in developing the country. Achieving the goals desired by the Kantor Pelayanan Pajak Pratama Pamekasan to find out the application of annual personal tax obligations to the directer general tax number regulation: PER-16/PJ/2016. The purpose of the study is to find out the annual income tax aplication of calculation, deposit, and reporting of artical 21 annual income tax on personal tax liability on Kantor Pelayanan Pajak Pratama Pamekasan and knowing the suitability of the application of calculation, deposit, and reporting of the annual 21 atical income tax on the sample with the current regulations. The type of research used is a mixed research method which the uses the results of research in the form of quantitative data and qualitative data by analyxing the comparision of the data obtained. The results of this study indicate the suitability of the application of calculation, deposit and reporting of income tax aticle 21 on an annual basis for individual taxpayers with the director general tax number regulation: PER-16/PJ/2016.